Understanding the case for low-carbon investment through bottom-up assessments of city-scale opportunities. (3rd April 2017) - Sudmant, Andrew Heshedahl; Gouldson, Andy; Colenbrander, Sarah; Sullivan, Rory; McAnulla, Faye; Kerr, Niall
Abstract : A growing body of literature suggests that an economic case may exist for investment in large-scale climate change mitigation. At the same time, however, investment is persistently falling well short of the levels required to prevent dangerous climate change, suggesting that economically attractive mitigation opportunities are being missed. To understand whether and where these opportunities exist, this article contrasts macro-level analyses of climate finance with micro-level bottom-up analyses of the scale and composition of low-carbon investment opportunities in four case study developing world cities. This analysis finds that there are significant opportunities to redirect existing finance streams towards more cost-effective, lower-carbon options. This would mobilize substantial new investment in climate mitigation. Two key explanations are proposed for the failure to exploit these opportunities. First, the composition of cost-effective measures is highly context-specific, varying from place to place and sector to sector. Macro-level analyses of climate finance flows are therefore poor indicators of the micro-level landscape for low-carbon investment. Specific local research is therefore needed to understand the opportunities for cost-effective mitigation at that level. Second, many opportunities require enabling governance arrangements that are not currently in place. Mobilizing new low-carbon investment and closing the 'climate finance gap' therefore requires attention to policy frameworks and financing mechanisms that can facilitate the exploitation of cost-effective low-carbon options. Policy relevance The importance of increasing investment in climate mitigation, especially in developing nations, is well established. This article scrutinizes four city-level studies of the scope for cost-effective low-carbon investment, and finds that significant opportunities are not being exploited in developing world cities. Enabling governance structures may help to mainstream climate considerations into investments by local actors (households, businesses and government agencies). While climate finance distributed through international bodies such as the Green Climate Fund may not always be a suitable vehicle to invest directly in disaggregated, local-level measures, it can provide the incentives to develop these governance arrangements.